Non-linear Distortion & its Reduction Techniques for Coherent Optical OFDM System: A Review - Joshi, Sunil; Sharma, Gaurav (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
In this paper the literature review is done for different compensation technique to reduce the nonlinear distortion for optical coherent system. Comparative analysis done so for dispersion compensation fiber, method of Fiber Bragg Grating, digital signal processing (DSP), pre and post symmetric-DCF techniques. The digital signal processing is very practical for all type of nonlinear distortion is minimized while dispersion technique is use to compensate the dispersion loss only and other methods are useful to reduce nonlinear distortion.